Configuration transitions of divacancies in silicon and germanium - O. P. Dolgolenko (Ядерна фізика та енергетика)
High-resistance samples p-Si (p0 = (1.63 - 7.09)·1011 cm-3) and n-Si (n0 = 1.19·1014 cm-3), grown by the float-ing zone melting after irradiation with fast neutron reactor at 320 C after isothermal and isochronal annealing were studied. The energy levels of divacancy in three charge states, depending on its configuration are deter-mined. Values of the energy levels of divacancies and A - center after their modification background impurities are considered.